Language: A Morpho-Syntactic Analysis - Lawati, Hari Chandra (Kirat Pragya किरात प्रज्ञा, 2026)
This paper examines the negation process that exists in the Limbu language, a pronominalized language (Grierson, 1909) of the Tibeto-Burman family from a typological perspective. It studies how the Limbu negative markers are formed and positioned within a sentence to change its truth value. There is obscureness in the Limbu negation process. So this study assists the learners (students) to understand the nature of the Limbu negation process and treat it accordingly. Information was collected from native speakers (teachers, Limbu writer and Limbu language user) and analyzed in a descriptive way and found that negation in Limbu is realized primarily through the affixation of the negative markers <mɛ-n>, <mɛ-nɛn>, <mɛll-n/nɛn>, <mɛ-ŋ/m/n> to the verb complex. The research underlines that negation interacts intricately with verbal inflection to the pronominal prefixes and the addition of negative suffixes, often resulting in a circumfix structure. The problems at the teacher’s level and persons who use Limbu language in literature and persons who use the Limbu language in their everyday life will be addressed. Deep study and clear understanding make the teaching-learning process purposeful.